Concentração da glutamina no leite materno cru maduro e após pasteurização - Souza, Soraia Silva de (2017)
The recommended milk for newborns (NB) is breast milk, and depending on their clinical condition or their mother, there is a need for the administration of pasteurized breast milk. It is also a fundamental preparation for enteral nutritional therapy in critical neonates, since breast milk has a high concentration of glutamine, considered as an important component in the clinical response of the neonate under aggression. Thus, the study analyzed the dosage of glutamine in the stages of raw mature breast milk and mature post-pasteurized breast milk. Objective: to evaluate the concentration of the amino acid glutamine in breast milk, in the mature lactation stage and after its pasteurization process. Methods: Twenty-six postpartum women were recruited, of whom 18 were eligible, 8 were excluded, and 10 postpartum women participated. Each sample of 100ml of milk in the mature stage (15th day of the puerperium), was collected individually at each address. The samples were divided into two fractions of 50 ml each, a fraction destined to the dosage of glutamine in raw mature mother's milk (LM) and the other fraction to be measured in pasteurized mature mother's milk (PML). Results: the mean age of the mothers was 25.40 years, the BMI was 26.79 kg / m2, the gestational age was 38.95 weeks, and the normal birth occurred in 60% of the patients. The concentration of glutamine in the LM group was 1.80 μMOL + 0.33 and in the LMP group was 1.93 μMOL + 0.44 (p> 0.05). Conclusion: the pasteurization process does not alter the concentration of glutamine in breast milk.